Association between smoking status and body composition parameters in a young adult population - Falbová, Darina; Beňuš, Radoslav; Vorobeľová, Lenka (Anthropological Review, 2023)
The purpose of this study was to analyze the association between smoking status and body composition parameters in 19–30 years old slovak population (mean age: 22,38 ± 2,34 years). The sample consisted of 379 individuals, including 143 men and 236 women. Body composition parameters were obtained using segmentation bioimpedance analysis. The results of our study showed that regular smokers had significantly higher values of waist circumference (p = 0.050), body mass index (p = 0.042), waist-toheight ratio (p = 0.027), fat mass index (p = 0.014) fat mass (p < 0.017), pecentual body fat (p = 0.008), trunk fat mass (FM, p = 0.008), leg fat mass (p = 0.029), and visceral fat area (p = 0.017) compared to non-smokers. Using correlation analysis, we detected an increase in FM (kg) values along with the frequency of smoking (r = 0,136; p = 0,009). Moreover, smoking positively correlated with coffee (r = 0.147; p = 0.002), energy drinks (r = 0.259; p < 0.001), and alcohol consumption (r = 0.101; p = 0.035). Smokers also added salt to their food more often (r = 0.132; p = 0.005) and worked less (r = -0.111; p = 0.025). In this study we confirmed the significant association of smoking with the body composition components, while it is responsible for higher adiposity in young adults.